Poole-Frenkel effect in amorphous poly(p-phenylene sulfide) - Campos, M. (1996)
The conductivity of poly(p-phenylene sulfide) (PPS) amorphous samples sandwiched between metallic electrodes has been studied as a function of applied voltage, temperature, and electrode material. The voltage (U) dependence of the currents for electric fields within the range 103-106 V/cm exhibits exp βU1/2 behavior with β = βSchottky below the glass transition temperature (Tg ≅ 90°C), and β = βPoole-Frenkel above Tg. Coordinated temperature measurements of dc currents with different metallic contacts and thermally stimulated currents (TSC) indicate, however, that the conductivity at T < Tg is consistent with the so-called anomalous Poole-Frenkel effect rather than the Schottky effect. Consequently, the p-type conductivity in amorphous PPS is proposed to be a bulk-limited process due to ionization of two different types of acceptor centers in the presence of neutral hole traps. © 1996 John Wiley & Sons, Inc.